Morphological Identification of Bacteria from Tuna Fish Isolates (Thunnus sp.) in Kondang Merak - Yulianto, Agus Tri; Yamindago, Ade (Aquatic Life Sciences, 2024)
Bacteria are microscopic organisms, and a small portion of them are pathogenic or harmful to living organisms. One example is bacteria that cause damage and decay in captured Tuna fish (Thunnus sp.) off the coast of Kondang Merak, Malang. Therefore, to determine the genus of bacteria found in Tuna fish (Thunnus sp.), bacterial morphology identification was conducted. Bacterial morphology identification was performed using methods involving the identification of colony and cell morphology, as well as bacterial respiration tests to enhance genus prediction accuracy. Bacterial morphology identification involved several testing stages, including Gram-staining, cell observation and measurement, motility testing, and bacterial respiration testing. The bacterial isolation samples from Tuna fish (Thunnus sp.) on TSA media consisted of 8 samples, namely 1a, 1b, 2a, 2b, 3, 4a, 4b, and 5, which were differentiated based on bacterial colony morphology. Based on the results of colony morphology identification, cell morphology, and respiratory testing, all 8 bacterial samples were manually identified with reference to identification books. The identification results showed that several samples had similar morphological characteristics. The bacterial morphology identification results for samples 2a and 2b were identified as belonging to the genus Aeromonas; samples 4a and 4b were classified into the genus Mesophilobacter; sample 1a was categorized into the genus Carnobacterium; and samples 1b, 3, and 5 belonged to the genus Vibrio.